Developing Reading Skill through Visualizing the text of Recount for Students of X Aph 1 at SMK N 6 Semarang in the Academic Year of 2015-2016 - Noor, Ahlis Qoidah (Lembaran Ilmu Kependidikan, 2016)
This Classroom Action Research ( CAR ) focused on how to develop students’ skill in Reading through visualizing the text of recount in the frame of Task Based Learning. The subject of the research was students of Grade X Aph 1 of SMK N 6 Semarang. The goal of the CAR is to identify the students’ skill in Reading and after having it then to develop them using the method Visualizing of recount text in the frame work of Task Based Learning (TBL). TBL is one type of the Student Centered Learning . The activities which were done in TBL were classified into the real task with their categories. Prabu ( 1987 ) suggested that there are 3 main categories from a task (1) information-gap, (2) reasoning-gap, and (3) opinion-gap. Whereas Willis ( 1996, pp. 135-136) informed that TBL consisted of the pre-task, the task cycle, and the language focus  then the writer did a range of activities as a manifestation of  TBL. As the component are goal and objectives, input, activities, teacher role, learner role, and setting. The CAR was done in two cycles where each cycle was in 2x2x45 minutes. It was for students of Grade X Aph1 .The result showed that the Reading skill increased from 15 % to 25 %. It was not satisfying result. In the second cycle, It developed to be 65 %. There was a little effort showed by the students with personal problem or family problem but at least the competence of the students increase from 15 % to 65 %. The rest of 35 % students consist of 25 % in big problem and 10 % students need some remedial assignment. After all activities done, the final skill in Reading was that there were 85 % students were skillful in Reading.